2017
DOI: 10.1002/smi.2744
|View full text |Cite
|
Sign up to set email alerts
|

A self‐determination approach to the understanding of the impact of physical activity on depressive symptoms

Abstract: The purpose was to test a new motivational sequence. It was hypothesized that more autonomous forms of motivation would predict the intensity of physical activity (PA), which in turn, would predict depressive symptoms. In order to evaluate self-determined motivation, the Self-Determination Index (SDI) was used. Because the reasons that can lead a person to engage in walking, moderate PA, or vigorous PA may be different, 3 independent self-determination indexes were measured (SDIWalking, SDIModerate, and SDIVig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 57 publications
2
14
0
4
Order By: Relevance
“…Perhaps the most important finding of the present study was that it was the VPA intensity which better predicted depressive symptoms, which is consistent with previous research 21 and with a very recent study that has assessed depression, anxiety and PA levels in North America under current social distancing guidelines during the COVID-19 pandemic. 25 Callow et al 25 found that LPA and VPA levels were independent contributors towards depression symptoms in older adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perhaps the most important finding of the present study was that it was the VPA intensity which better predicted depressive symptoms, which is consistent with previous research 21 and with a very recent study that has assessed depression, anxiety and PA levels in North America under current social distancing guidelines during the COVID-19 pandemic. 25 Callow et al 25 found that LPA and VPA levels were independent contributors towards depression symptoms in older adults.…”
Section: Discussionsupporting
confidence: 92%
“… 4 , 18 On the other hand, it has been indicated that PA impacts positively on mood 19 and affect. 20 It may also have beneficial effects on depressive symptoms 21 , 22 and may prevent depression promoting social support or resilience. 23 Unfortunately, the optimal type (e.g., aerobic, strength) and dose (e.g., duration, frequency, intensity and/or volume) remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…To assess self-determined motivation, the self-determination index (SDI) was used [40], calculated on the basis of the following formula: 3x intrinsic motivation, 2x integrated regulation, 1x identified regulation, −1x introjected regulation, −2x external regulation and −3x de-motivation. This index has been shown to be valid and reliable in several works [41][42][43], being used to obtain a value that allows for quantifying the level of self-determination.…”
Section: Instrumentsmentioning
confidence: 99%
“…Physical activity has been linked to an increase in these substances (Craft & Perna, 2004). It has been observed as a moderator between them and depressive symptoms too (Cecchini-Estrada, Fernández Río, Méndez-Giménez, Carriedo, & Arruza, 2017;Rethorst, et al, 2011). Melancon, Lorraine and Dionne (2012) support the idea that an increase in individuals' neurotransmitter levels could explain the antidepressant effects of physical activity.…”
Section: Introductionmentioning
confidence: 98%